Trends in Sustainable Consumption: Adoption of Halal Packaged Food among Millennial - Jusman, Rahmayani; Razak, Syaparuddin; Marzuki, Sitti Nikmah (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
This study aims to explore the relationship between intention, perceived behavioral control, and the substantive impact of intention in adopting halal packaged foods among the millennials. This study applied the Theory of Planned Behavior framework. A quantitative descriptive research method was employed, with data collected through questionnaires from two hundred respondents selected via simple random sampling in July-August 2023. The results showed that intention and perceived behavioral control play key roles in adopting halal packaged foods. Factors such as sharia compliance, attitude toward halal food, subjective norms, and perceived behavioral control significantly influence the formation of intention. The novelty of this research lies in the integrative examination of various factors influencing the intention to adopt halal packaged foods within the context of Indonesian society, providing new insights into the interaction between psychological and religious factors. The implications of these findings highlight the importance of enhancing halal literacy among consumers to strengthen positive attitudes toward halal food and sharia compliance. Social environmental support and strengthening behavioral control can also increase the intention to adopt halal packaged foods. Recommendations for stakeholders include providing clear and educational information about the benefits and importance of halal food, as well as developing marketing strategies that emphasize these aspects to encourage broader adoption within the community.